FUNCTIONAL AND PERSONALIZED NUTRITION AS NEW GASTRONOMIC DIRECTIONS - Vladimir A. Ermolaev (Russian Studies in Culture and Society)
In the article, the author examines two relatively new gastronomic trends, such as functional and personalized types of nutrition. As follows from the names, the directions pursue the goals of ensuring the functioning (of the organism) and compliance with the lifestyle (of a person).